Education methods of Brazilian jiu-jitsu with biomechanics - sangwoo Jeon (Firenze University Press, 2020)
Jiu-jitsu is a martial art that can be used by men and women of all ages in the world and is trained by many people. Jiu-Jitsu (guidance), the ancestor of Jiu-Jitsu, is the technique used by Samurai at the last moment. They demonstrate that drinking is inefficient when losing weapons at close range and enemy opponents. Berries and clicks are more effective for survival. Jiu-Jitsu, now famous around the world, was shown in Brazil by Mitsuyo Maeda (Conde Koma) in Japan. Brazilian Jiu-Jitsu moves to a position that is advantageous for his bare hands and uses opponents and cookers to control the opponent. Brazilian Jiu-Jitsu has the advantage that small people can beat large ones. Adjust the ground technology such as moderating, strangling, and clicking to use the technology more efficiently than defeat with power. It has been established that jiu-jitsu can be useful for martial arts and self-defense techniques as time goes by, but few papers have spelled it out, especially in Korea. Also, many Jiu-Jitsu stands in Korea and claim that the best way of raising their organization is the best, and many Jiu-Jitsu practitioners in South Korea teach from the Jiu-Jitsu teaching method Was given a one-sided training. Therefore, in this paper, we grasped the vitality principle of Jiu-Jitsu and examined the appropriate training method.